2015
DOI: 10.1177/0022219415617164
|View full text |Cite
|
Sign up to set email alerts
|

First-Year College Students With ADHD and/or LD

Abstract: Students with attention-deficit/hyperactivity disorder (ADHD) and/or learning disabilities (LD) experience significant challenges in making the transition from high school to college. This study examined the ways first-year college students with ADHD, LD, ADHD+LD, and comparison peers differ in engagement, core self-evaluation, high school preparation behaviors, and goals/expectations. Participants were from the 2010 Cooperative Institutional Research Program Freshman Survey, including students with ADHD ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Kuh, Cruce, Shoup, Kinzie, and Gonyea (2008) found that first-year college students who engaged in educationally purposeful activities and studied more hours per week earned higher grade point averages (GPAs) and were more likely to persist in college. Conversely, a study done by DuPaul, Pinho, Pollack, Gormley, and Laracy (2015) found that college students with disabilities demonstrate significantly less school engagement than their peers without disabilities, a finding consistent with the higher attrition rate of these students in college (Stodden et al, 2001).…”
Section: Engagementmentioning
confidence: 83%
“…Kuh, Cruce, Shoup, Kinzie, and Gonyea (2008) found that first-year college students who engaged in educationally purposeful activities and studied more hours per week earned higher grade point averages (GPAs) and were more likely to persist in college. Conversely, a study done by DuPaul, Pinho, Pollack, Gormley, and Laracy (2015) found that college students with disabilities demonstrate significantly less school engagement than their peers without disabilities, a finding consistent with the higher attrition rate of these students in college (Stodden et al, 2001).…”
Section: Engagementmentioning
confidence: 83%
“…We recruited college students with ADHD as they have been a growing but relatively understudied population. As students, they face an increased demand for self-regulation, time management, and organization to succeed in what is a particularly formational period of their lives (DuPaul, Pinho, Pollack, Gormley, & Laracy, 2017; Gray, Fettes, Woltering, Mawjee, & Tannock, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This process may happen by comparison, engagement, consensus or experience (24) . Studies (25) indicated that academic self-assessment is positively associated with student performance.…”
Section: Discussionmentioning
confidence: 99%